INFLUENCE OF HUDUMA CENTRE INNOVATION STRATEGIES ON GOVERNMENT SERVICE PERFORMANCE IN KENYA; A CASE OF KAKAMEGA COUNTY - KAGASI, VIOLET; SANGORO, MR. OSCAR; ROMAN, MR. AKETCH; OIRERE, Dr. DORCAS (IJRDO - Journal of Business Management, 2016)
In 2013, the government introduced the concept of Huduma Centres as a service deliverystrategy to transform public service delivery by providing citizens access to various publicservices and information under one roof. The study adopted a descriptive survey design. In thisstudy, the target population was10,595 respondents comprising of 10,560 customers, 30operative employees and 5 managerial employees. The researcher sampled 2675 respondents byuse of purposive sampling to select 5 managerial employees, stratified sampling to select 70customers and census sampling to select 30 operative employees. The study used questionnaires,interview schedules and observation checklists as a means of collecting data which was thenanalysed using both descriptive and inferential statistics and presented in form of frequency,percentages and tables. This was done in sequence of objective based on hypothesis testing. Thechi square and ANOVA tests were used to give the significance of the relationship between theindependent and dependent variables of the objectives. It is hoped that the findings of the studymay be utilised by Huduma Centre management in order to improve government serviceperformance. The three contextual factors explained 34.5% of its variation (R2=.345, P=0.000).However, each of the factors had varied degree of effect on the government service performancewith level of technology, management style and government policy in that order. The overallstudy recommendation is that public institution should use innovation strategies to streamlineoperations, capture new markets and set themselves apart in service delivery in publicinstitutions which are known to offer substandard services to the tax payers.